The ineffectiveness of the rules for the execution of food sentences for children and adolescents - Príncipe Mena, Abner (2020)
The purpose of this article is to develop some reflections on the maintenance process at the sentencing stage; since it constitutes the procedural stage that has been presenting the greatest inconveniences to the detriment of the defendants belonging to children. For this reason, the importance of having simple and suitable rules and procedures as well as a protective work and interpretation of the jurisdiction at the time of executing the sentence is highlighted; in order to effectively guarantee the fundamental right to obtain alimony.